Electrochemically Induced Intermolecular Cross-Dehydrogenative C–O Coupling of β‑Diketones and β‑Ketoesters with Carboxylic Acids - Bityukov, Oleg V; Matveeva, Olesya K; Vil’, Vera A; Kokorekin, Vladimir A; Nikishin, Gennady I; Terent’ev, Alexander O (Journal of organic chemistry, 2019)
The electrochemically induced cross-dehydrogenative C–O coupling of β-diketones and β-ketoesters (C–H reagents) with carboxylic acids (O–H reagents) was developed. An important feature of this reaction lies in the selective formation of intermolecular C–O coupling products in high yields, up to 92%, using DMSO as a solvent with a broad substrate scope in an undivided cell equipped with carbon and platinum electrodes at high current density. Electric current acts as a stoichiometric oxidant.